Sketching as a key instrument for design in architectural education (Architecture Image Studies, 2020)
With this article it was intended to approach sketching as a form of representation and its relation to design in architectural education. For this purpose, recent publications focused on sketching and its role in design processes were reviewed, using the theoretical and drawn work of Álvaro Siza Vieira as a guiding thread. Firstly, it was sought to determine the nature of sketching, its purposes and its particularities in educational context. Secondly, the role of sketching in design was explored considering the procedures of recognition, transformation and presentation.